Desain Asset Visual Game Mobile Matematika - Andreatono Nathaniel; Saiful Yahya (MAVIS : Jurnal Desain Komunikasi Visual, 2023)
Mathematics is one of the compulsory subjects for students in Indonesia. Mathematics is one of the quality of learning subjects, especially math during the epidemic seoson, the learning materials are effective, interesting ang not boring for students. One way is to create educational games using mobile phones. Educational game is an Android based mobile game that makes it easier for users to use it anywhere and anytime than other platforms, same as a computer. Therefore, the problem posed in this research is How to generate mathematical mobile game image assets? Solution to this research problem is how to design visual assets with a natural theme. So create some icons, buttins and background design with forest design, wood design and another math related objects. It is then incorporated into the final design. End of the result from this research is visual game assets can be used to make games easy to operated and enjoyable, especially for elementary student in grades 3 and below.